Faster image compression (LZW algorithm) technique using GPU parallel processing - Soobhee, Ateeq-Ur-Rahman; Ruma, Kamrun Nahar; Ahsan, Md. Fakhrul; Hossain, F. M. Fahmid (BRAC University, 2018)
Cataloged from PDF version of thesis report.